Prevalence of Parasitic Diseases in Carps in Bheries of West Bengal, India - Guguloth, Balaji; Ramudu, Kurva Raghu; Subbaiah, Kanasi; Rajesh, Sandya Chinna (International Journal of Bio-resource and Stress Management, 2013)
Parasitic prevalence is more in carps in Bheries of West Bengal region, India because all the farmers are using seawage waste water for their culture. The seawage water contains 99% of water and 1% of other materials include pathogens like bacteria, virus, and large parasites include external, internal parasites. It can cause first primary infection, it is the main source for the secondary bacterial infection and it can cause mortality in culture fishes. The farmer has so much economic loss due to this parasitic diseases. It very important to study the parasitic diseases in Bheries of West Bengal region.